2016
DOI: 10.1007/s00018-016-2145-x
|View full text |Cite
|
Sign up to set email alerts
|

The epigenetic role of vitamin C in health and disease

Abstract: Recent advances have uncovered a previously unknown function of vitamin C in epigenetic regulation. Vitamin C exists predominantly as an ascorbate anion under physiological pH conditions. Ascorbate was discovered as a cofactor for methylcytosine dioxygenases that are responsible for DNA demethylation, and also as a likely cofactor for some JmjC domain-containing histone demethylases that catalyze histone demethylation. Variation in ascorbate bioavailability thus can influence the demethylation of both DNA and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
125
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(131 citation statements)
references
References 161 publications
(175 reference statements)
1
125
0
1
Order By: Relevance
“…The benefit of high doses of ascorbate in broad-spectrum cancer treatment was initially reported by Cameron and Pauling [77]; however, subsequent trials have either shown promising benefits in certain circumstances, or have provided no detectable advantages at all [78][79][80][81][82][83][84]. Nevertheless, it remains possible that vitamin C supplementation can reverse global loss of 5hmC [6] and hypermethylation of tumor-suppressor genes [75,76]. In support of this proposition, it has been found that a high proportion of cancer patients are actually deficient in vitamin C [84].…”
Section: Reprogrammingmentioning
confidence: 99%
See 2 more Smart Citations
“…The benefit of high doses of ascorbate in broad-spectrum cancer treatment was initially reported by Cameron and Pauling [77]; however, subsequent trials have either shown promising benefits in certain circumstances, or have provided no detectable advantages at all [78][79][80][81][82][83][84]. Nevertheless, it remains possible that vitamin C supplementation can reverse global loss of 5hmC [6] and hypermethylation of tumor-suppressor genes [75,76]. In support of this proposition, it has been found that a high proportion of cancer patients are actually deficient in vitamin C [84].…”
Section: Reprogrammingmentioning
confidence: 99%
“…One of the most recently discovered fields that vitamins A and C impact upon is epigenetics [5][6][7]. New research has shown that both vitamins drive active removal of DNA methylation in embryonic stem cells (ESCs) by enhancing the same family of ten-eleven translocation (TET) enzymes, and in doing so, help erase DNA methylation and the epigenetic memory encoded by it to improve the reprogramming of differentiated cells to an embryonic-like state.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, AA is also a cofactor of enzymes that carry out methylation of histones, which also provides epigenetic regulation of gene activity, in particular by changing the concentration and bioavailability of AA in different sites of organs and tissues. This activity is important in the development of pathologies such as neurodegenerative and oncological diseases in the absence of AA [10].…”
mentioning
confidence: 99%
“…For example, vitamin C has been shown to be a cofactor for methylcytosine dioxygenases, which are enzymes for DNA demethylation, an important crossroad in epigenetic regulation [37] [38]. Curcumin is a complementary therapy that may be helpful for the treatment of a variety of diseases because of its anti-inflammatory, antiangiogenic, antioxidant, and antiproliferative effects [39] [40] [41].…”
Section: Discussionmentioning
confidence: 99%